Learning to Consult and Collaborate in the High School: A Two-Year Study of Perceptions from University Student Team Members - Eleanor T. Migliore; Angela Breidenstein (Networks: An Online Journal for Teacher Research, 2003)
Collaboration in the schools is an important intervention for providing services to students and staff members. The majority of studies regarding collaborative consultation between school psychologists and teachers have been conducted at the elementary and middle school levels. Further, little has been written about teaching collaborative consultation at the university level to preservice educators.This article describes a two-year project designed to teach collaboration at the university level to two groups of high school teacher interns and school psychology students enrolled in separate courses. Teacher trainees identified problems within their classrooms with which they needed assistance and school psychology students collaborated with them to find appropriate interventions. The process was examined at the end of each spring semester for two years through focus groups led by the two university professors. Analysis of the group interactions indicated similarities and differences between the two student groups. First-year students spent a great deal of time and energy establishing a relationship with their partners and supporting this positive interaction, however, specific, practical interventions were neglected. Students in the second-year group were better able to collaborate on the implementation of actual interventions. This was attributed to additional structure and accountability measures added to the courses. Recommendations for future collaboration training experiences are outlined by the authors.